PENGARUH SARI KURMA TERHADAP PROLAKTIN DAN PENGELUARAN ASI PADA IBU POSTPARTUM DI BPM PIPIN HERIYANTI YOGYAKARTA TAHUN 2017 - Yulinda, Dwi; Azizah, Imroatul (Media Ilmu Kesehatan, 2017)
Background: Breastfeeding is exceptionally superior, giving mother and infants distinct and subtastial physical, mental, and developmental health advantages. Palm fruit has content of phytonutrients with antioxidant properties and galactagogues to help increase their milk supply in the early postpatum days. The lowest exclusive brest feeding rates in DIY is in the city of Yogyakarta. Exclusive breast feeding improves infant immunity so as to minimize the occurrence of diarrhea, constipation, fever that is caused by some allergic reactions. Objectifive: :This study aimed to analyze the relationship between date palm fruits on postpartum to prolactin and volume of breast milk Method: Research was conducted on maternal postpartum which is divided into two groups. They are the control group; and the treatment group which was given dates palm fruit. Breast milk volume and prolactin was measured at 3 day after labor. The analytical method used is Student T-test. Results: Date Palm fruits increased prolactin and volume of breast milk which was significantly on firstweek breastfeeding increase in the treatment group compared to the control group at p <0.05. Conclusion: Date Palm fruits is one of the alternatives that can be done to improve the success of exclusive breast feeding on postpartum. Key Words: Date palm fruit, postpartum, prolactin and volume of breast milk